Analisis Brand Respons Pada Neynis Food Berdasarkan Data Media Sosial TikTok - Hendrawan, Angga (Jurnal Industri Kreatif dan Inovatif, 2023)
TikTok is a social media platform that is experiencing a growth in user numbers globally, including Indonesia.Social media has become an effective medium for businesses to deliver marketing communications. The existenceof TikTok has helped a number of businesses gain popularity, including a culinary business called Neynis Food.This research aims to analyze brand responses to Neynis Food after facing a number of viral events. The analysiswas carried out using the brand resonance model which consists of brand judgments and brand feelings. Datacollection was carried out using a descriptive exploratory method to explore and explain the response of TikToksocial media users to the Neynis Food brand which was associated with a number of viral events. The datacollected and used comes entirely from search results owned by the social media application TikTok. The resultsof this research indicate that brand responses to Neynis Food are negative and require follow-up action to improvethem.